Impacts of Store Trust Antecedents on Willingness to Disclose Personal Data in Online Shopping - Urbonavičius, Sigitas; Degutis, Mindaugas; Zimaitis, Ignas; Skare, Vatroslav (Organizations and Markets in Emerging Economies, 2023)
Personal data disclosure is crucially important to modern business, and specifically – to online stores. It is largely predicted by the willingness to disclose personal data that significantly varies among emerging economies due to impacts of numerous factors. One of the important factors that impacts willingness to disclose personal data in online shopping is trust in an online store. However, the importance of trust in a store partly occurs because it mediates effects of other antecedents. This study conceptualizes three groups of important antecedents: personal, infrastructural and store-related factors. The study tests indirect effects of the most typical factors from each group: general trust (personal factor), legal regulations (infrastructural factor) and presence of an off-line selling channel in addition to the online channel offered by a store (e-store factor) on willingness to disclose personal data online. The findings show that all these factors, mediated by store trust, have significant positive effects on willingness to disclose personal data. The findings contribute to the knowledge of the groups of factors that impact willingness to disclose personal data online and help to set directions for future research.Acknowledgement: this project has received funding from the Research Council of Lithuania (LMTLT), Agreement No S-MIP-19-19
Keywords: willingness to disclose personal data; store trust; perceived regulatory effectiveness; selling channels